C-Reactive Protein: Friend or Foe? Phylogeny From Heavy Metals to Modified Lipoproteins and SARS-CoV-2 - Torzewski, Michael (Frontiers in Cardiovascular Medicine, 2022)
Animal C-reactive protein (CRP) has been found in every organism from arthropods to humans where its presence has been sought implying that these proteins have important functions which, teleologically speaking, merit preservation. About 500 million years of evolution teach us that there is a continuous interplay between emerging antigens and components of innate immunity. The most archaic physiological roles of CRP seems to be detoxication of heavy metals and other chemicals followed or accompanied by an acute phase response and host defence against bacterial, viral as well as parasitic infection. On the other hand, unusual antigens have emerged questioning the black-and-white perception of CRP as a being invariably beneficial. Such antigens came along either as autoantigens like excessive tissue-stranded modified lipoprotein due to misdirected food intake linking CRP with atherosclerosis with an as yet open net effect, or as foreign antigens like SARS-CoV-2 inducing an uncontrolled CRP-mediated autoimmune response. The latter two examples impressingly demonstrate that a component of ancient immunity like CRP should not be considered under identical “beneficial” auspices throughout phylogeny but might effect quite the reverse as well.